Analisis Upaya Peningkatan Capaian Standar Pelayanan Minimal (SPM) Pelayanan Kesehatan Orang Terduga Tuberkulosis (TB): Analysis of Efforts to Improve the Achievement of Minimum Service Standards (SPM) for Health Services for People Suspected of Tuberculosis (TB) - Handayani, Mega indah; Yeni, Rahma (Journal of Public Health Education, 2025)
Introduction: Minimum Service Standards (SPM) for tuberculosis is an important pillar in efforts to control this disease. Implementing SPM can overcome various challenges, such as limited resources, increasing public awareness, supporting the implementation of national policies, and optimizing program implementation. Objectives: To analyze efforts to improve the achievement of SPM for TB services at the Sawangan Health Center, Depok City, in 2024. Method: This research uses a descriptive qualitative approach to explore the implementation of Minimum Service Standards for tuberculosis at the UPTD Puskesmas Sawangan, Depok. Data collection was carried out through in-depth interviews with key, main and additional informants during the period May-July 2024. Informants were selected based on their role in the tuberculosis control program at the health center. Result: Several obstacles hinder the achievement of TB SPM. Human resources are insufficient both in quantity and competence, with outdated training and no formal assignment for the TB program officer. Infrastructure is lacking—TB services are merged with the ARI clinic and lack diagnostic tools like TCM and BSC. Although TB medication is adequately supplied and funding from APBN and APBD is sufficient, low motivation among officers due to absence of incentives affects service delivery. Administrative processes meet standards, but patient adherence to treatment remains a challenge. Conclution: Barriers to achieving TB SPM at the Sawangan Health Center include limited human resources, inadequate facilities, and low staff motivation. Enhancing capacity, infrastructure, and incentive systems is essential to improve program outcomes.